Recovery of Potassium from Incineration Ash of Chicken Dropping (IACD) by Sulphuric Acid Leaching Followed by Adsorption Using Orange Waste Gel (Journal of Nepal Chemical Society, 2021)
Two types of leaching solution namely; aqua-regia and 1MH2SO4 were investigated for the leaching of K(I) from incineration ash of chicken dropping (IACD), in this study. SOJR and Na(I)-SOJR adsorbents were prepared from orange juice residue for the adsorption of K(I) from IACD leached liquor, which was compared with READF-(PG) and 200CT resin. The characterization of IACD leaching was done in EDX and FTIR spectroscopic techniques. Aqua-regia solution completely dissolved IACD and all the adsorbents. One molar sulphuric acid (1MH2SO4) solution was optimized for effective leaching of K(I) from the IACD sample. SOJR, Na(I)-SOJR, and 200CT adsorbed K(I) from leached liquor whereas K(I) was insignificantly adsorbed onto READF-(PG). The desorption of adsorbed K(I) could be successfully done by H2SO4 solution for recovery and adsorbent regeneration for further usage. From comparisons, Na(I)-SOJR investigated in this study was found to be equally effective with a commercially available cation exchanger (200CT resin). Therefore, a new method of H2SO4 leaching of IACD followed by adsorption using Na(I)-SOJR investigated in this work can be an economic, environmentally benign, and promising technique for the recovery of K(I) ion from leach liquor of IACD.